2016
DOI: 10.5993/ajhb.40.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Motivations to Prevent Heart Disease among Puerto Ricans

Abstract: Objectives We performed a qualitative assessment of Puerto Ricans’ knowledge and perceptions of cardiovascular disease (CVD), and motivations/barriers and preferences to participate in community/ clinical programs for CVD-prevention. Methods Four guided focus group discussions were conducted on a total of 24 Puerto Ricans, aged 40–60 years in Boston, MA. Results Participants were aware of CVD, but less knowledgeable about its prevention. They perceived it as serious, and either had CVD or knew someone who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Some challenges we encountered, such as, weather, transportation, and health-related challenges had been previously reported in younger Latinos [27,28] or non-Latino white older adults [29,30], however, in our three studies we found them to be frequent among older Latinos as well. For example, the weather was a major challenge for the BAILAMOS study but was not a challenge for ¡En Forma y Fuerte!…”
Section: Retention and Attendance-related Challenges And Solutionsmentioning
confidence: 40%
“…Some challenges we encountered, such as, weather, transportation, and health-related challenges had been previously reported in younger Latinos [27,28] or non-Latino white older adults [29,30], however, in our three studies we found them to be frequent among older Latinos as well. For example, the weather was a major challenge for the BAILAMOS study but was not a challenge for ¡En Forma y Fuerte!…”
Section: Retention and Attendance-related Challenges And Solutionsmentioning
confidence: 40%
“…According to a qualitative analysis by Mattei et al in the United States (N=24), the prevention of CVD is assisted by health education, healthcare and therapy in health and via social media. 19 On the basis of a qualitative study conducted in Kandula (n=36), patients are helped to improve actions, such as smoking, unhealthy diet and excessive consumption of alcohol. Patient therapy also encompasses multiple aspects that facilitate good health between patients and the community as different caregivers, such as nutritionists, nurses, physiotherapists and physicians, may provide counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that Latinos have a strong willingness and trust to participate in biomedical studies, and are motivated by the perceived importance of the study topic and a desire to acquire and contribute to new knowledge [ 61 , 63 65 ]. While material incentives are not always a strong motivation for participation in health programs among Puerto Ricans [ 66 ], they should be fair and commensurate to the time and effort of the study [ 60 ]. Additional incentives such as health literature or services, transportation, raffles, food, or pastime activities, may also be valuable [ 61 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…While material incentives are not always a strong motivation for participation in health programs among Puerto Ricans [ 66 ], they should be fair and commensurate to the time and effort of the study [ 60 ]. Additional incentives such as health literature or services, transportation, raffles, food, or pastime activities, may also be valuable [ 61 , 66 ].…”
Section: Discussionmentioning
confidence: 99%